Risk Factor for Cardiac Permanent Pacemaker Infection - Shah, Hammad; Mehmood, Mazhar; Salahudin, Momin; Altaf, Afrasyab (Journal of Nepal Health Research Council, 2019)
Background: Cardiac pacemaker infections have increased globally due to increase in demand and lack of adequate knowledge about its significantly contributing risk factors. This study was therefore aimed to determine the prevailing causative microbes and risk factors of both single and dual chamber permanent pacemaker infections. Methods: This was a retrospective case control study. Cases were selected as culture positive swab, Temporary pacemaker wire or catheter were matched with three controls for each variable using chi square test. Multivariate regression analysis was done to determine risk factors. Results: Among 47 cases, 23.4% cases were infected by methicillin resistant staph aureus, 14.9% by methicilin susceptible Staphylococcus aureus, 10.6% by pseudomonas, 8.5% by escherichia coli and 6.4% by klebsiella. Temporary pacemaker/Central line placed >24 hours ago before permanent pacemaker implantation, remnant pacemaker leads, corticosteroid use, no antibiotic prophylaxis, diabetes, smoking and non-absorbable stitches had statistically significant association with permanent pacemaker infection using multivariate regression model analysis. Chronic obstructive pulmonary disease and non-absorbable stitches had a non-significant association. Conclusions: Temporary pacemaker/Central line placed >24hours before permanent pacemaker implantation, remnant pacemaker leads, corticosteroid use, no antibiotic prophylaxis, diabetes, smoking and use of non-absorbable stitches are risk factors for permanent pacemaker infection. Staph aureus is the most prevalent microorganism causing infection.Keywords: Causes; dual chamber; Infectison; permanent pacemaker; risk factor; single chamber.